Genetic variation within cassava germplasm in response to potassium - El-Sharkawy, Mabrouk A.; Cadavid López, Luis Fernando (Cambridge University Press, 2000)
As cassava is grown mostly by small resource-limited farmers throughout the tropics on low-fertility soils with little fertilization and, due to the large potassium (K) export in harvested roots, genotypes that tolerate low-K soils and respond to K fertilization are warranted. The objective of this study was to evaluate cassava germplasm and identify such genotypes. Fourteen cultivars of cassava (Manihot esculenta) selected from the core germplasm at CIAT were grown under rainfed conditions for ten months over five consecutive seasons in Inceptisols either with no K application or with 50, 100 or 200 kg K ha?1 applied annually together with adequate nitrogen and phosphorus. All cultivars responded to K application both in terms of root and shoot biomass with the highest yields obtained by CM 507-37 and M Ven 25 in the absence of K application and at high K levels. These cultivars had the highest adaptation indices to low K and the highest K use efficiency for total biomass production. CM 507-37 had the highest K use efficiency for root production at all K levels. Thus, it is desirable to use this material for breeding cassava which is adapted to low-K soils and is able to respond to fertilizer application. However, because of the high hydrocyanic acid (HCN) content in their roots, these cultivars should be crossed with genotypes that are low in HCN, such as HMC-1 and M Cub 74, in order to select lines with both high K use efficiency and low HCN for fresh cassava consumption. Root HCN contents were significantly reduced by application of K across all cultivars. Application of K fertilizer to low-K soils is warranted to minimize health hazards when fresh cassava is used for human consumption.